The effect of mechanical traction on cervical radiculopathy: protocol for the TracCerv2 single-blind, randomised controlled trial - Grégoire Cormier; Chloé Moreau; Emilie Scalisi; Lydie Pastor; Thomas Rulleau (BMC Complementary Medicine and Therapies)
Abstract Objectives To evaluate the effect at 3 months of an intensive cervical traction protocol on disability in people with cervical radiculopathy and compare with placebo traction. Design The trial is national, multi-centre, randomised, placebo-controlled and single-blinded. It began in March 2024 and will end in September 2027. Participants are allocated to receive mechanical cervical traction or placebo mechanical cervical traction. Setting Seven hospitals in France. Participants We will include 206 individuals with cervical radiculopathy diagnosed 3 to 12 months previously, hospitalised to undergo mechanical traction. Main inclusion criteria: age ≥ 18 years, Neck Disability Index ≥ 15/50 points and presence of ≥ 3 of 4 diagnostic signs of cervical radiculopathy. Interventions All participants undergo 2 × 30 min of traction per day for 5 consecutive days. For mechanical cervical traction, the maximum weight is ≤ 12 kg and for placebo traction ≤ 600g. Main outcome measures The primary outcome is disability (Neck Disability Index), secondary outcomes include pain related outcomes, medication consumption, surgery and days off work. Results This study will provide a robust evaluation of the mid-term effectiveness of mechanical traction on disability in chronic cervical radiculopathy. The results will demonstrate whether a simple technique involving a short, intensive protocol reduces the duration of disability and pain. Conclusions The availability of robust evidence supporting or refuting the use of cervical traction as part of the management of cervical radiculopathy will enable optimisation of treatment. The results could lead to the drafting of evidence-based recommendations regarding the use of mechanical traction to treat cervical radiculopathy. Clinial trial registration number ClinicalTrials.gov (NCT05952167).